The effect of mourning for parents affected by Covid 19 on the mental health of children and adolescents in Tehran (Case study) - Beshkouh, Majid; Shahabzadeh, Sedighe (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2020)
Background and Aim: In the current high-risk situation, it is essential to identify children and adolescents prone to psychological disorders at different classes of society with mental health endangered by parental grief to maintain their mental health using appropriate psychological strategies and techniques. Therefore, the present study aimed to examine the effect of Parental grief due to COVID-19 on the mental health of children and adolescents in Tehran (case study). Methods: The research was applied in terms of purpose, and descriptive survey in terms of data collection. Its statistical population consisted of parents, children, and adolescents in Tehran in the spring and summer of 2020. The sample size of the study was equal to 50 people who were selected voluntarily. The research tools included the Hogan Grief Reaction Checklist (HGRC) (2001), and Goldberg-Hill Mental Health Questionnaire (1972). Data were analyzed by regression analysis and SPSS23. Results: The results indicated that parental grief due to COVID-19 and each of its components, namely frustration, panic behavior, blame and anger, isolation, confusion, and personal growth of children and adolescents had significant effects. Therefore, each dimension of Parental grief, namely confusion, personal growth, blame and anger, panic behavior, isolation, and frustration were respectively the best predictors of the dependent variable (criterion), namely the mental health of children and adolescents. Conclusion: In the current high-risk situation, it is essential to identify children and adolescents prone to psychological disorders at different classes of society with mental health endangered by Parental grief to maintain their mental health using appropriate psychological strategies and techniques.